NTCP Deficiency Affects the Levels of Circulating Bile Acids and Induces Osteoporosis - Yang, Fangji; Xu, Wenxiong; Wu, Lina; Yang, Luo; Zhu, Shu; Wang, Lu; Wu, Wenbin; Zhang, Yuzhen; Chong, Yutian; Peng, Liang (Frontiers in Endocrinology, 2022)
Background The p.Ser267Phe mutation in the SLC10A1 gene can cause NTCP deficiency. However, the full clinical presentation of p.Ser267Phe homozygous individuals and its long-term consequences remain unclear. Hence, in the present study, we characterized the phenotypic characteristics of NTCP deficiency and evaluated its long-term prognosis. Methods Ten NTCP p.Ser267Phe homozygous individuals were recruited and a comprehensive medical evaluation with a 5-year follow-up observation was performed. The phenotypic characteristics of NTCP deficiency were also demonstrated using an NTCP-global knockout mouse model. Results During the 5-year follow-up observation of ten NTCP p.Ser267Phe homozygous adults, we found that the most common phenotypic features of NTCP deficiency in adults were hypercholicemia, vitamin D deficiency, bone loss, and gallbladder abnormalities. The profile of bile acids (BAs) in the serum was significantly altered in these individuals and marked by both elevated proportion and concentration of primary and conjugated BAs. Moreover, the NTCP deficiency led to increased levels of serum BAs, decreased levels of vitamin D, and aggravated the osteopetrotic phenotype induced by estrogen withdrawal in mice. Conclusions Both mice and humans with NTCP deficiency presented hypercholanemia, and were more prone to vitamin D deficiency and aggravated osteopetrotic phenotype. Therefore, we recommend monitoring the levels of BAs and vitamin D, bone density, and abdominal ultrasounds in individuals with NTCP deficiency.